2022
DOI: 10.1037/apl0001003
|View full text |Cite
|
Sign up to set email alerts
|

Promotive and prohibitive ethical voice: Coworker emotions and support for the voice.

Abstract: Despite the importance of ethical voice for advancing ethics in organizations, we know little about how coworkers respond to ethical voice in their work units. Drawing on the fundamental approach/avoidance behavioral system and the promotive and prohibitive distinction in the voice literature, we distinguish between promotive and prohibitive ethical voice and propose that they engender different emotionselevation (an approach-oriented moral emotion) and feelings of threat (an avoidance-oriented emotion), respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 107 publications
(205 reference statements)
0
47
0
1
Order By: Relevance
“…Conceptually related to but distinct from ethical taking charge, ethical voice is focused on verbally suggesting ideas for improving the ethical situation and challenging the status quo (Chen & Treviño, 2022; Rees et al, 2013). Ethical voice can thus be described as an employee's expression of concerns about violations of ethical standards (Morrison, 2011).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations
“…Conceptually related to but distinct from ethical taking charge, ethical voice is focused on verbally suggesting ideas for improving the ethical situation and challenging the status quo (Chen & Treviño, 2022; Rees et al, 2013). Ethical voice can thus be described as an employee's expression of concerns about violations of ethical standards (Morrison, 2011).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…As extant research has shown, both employees and organizations greatly benefit when employees express ethical voice, through improved leadership behaviors (e.g., Babalola et al, 2022) and ethical performance (Huang & Paterson, 2017). Thus, finding ways to encourage more ethical voice within organizations continues to be an issue of significant theoretical and practical importance (Babalola et al, 2022; Chen & Treviño, 2022). In short, both ethical voice and ethical taking charge serve as two related but distinct forms of ethically focused proactive behavior that effectively capture employees' desire to make a positive difference in their organizations (Babalola et al, 2022; Kim et al, 2015; Kim & Liu, 2017; Weiss & Morrison, 2019).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…Employees' acquiescence voice definition emphasizes expressing support for work-related practices and out of a sense of inability to make a difference (Maynes & Podsakoff, 2014). However, when employees make many suggestions, inevitably, some suggestions will not be regarded as useful, value-added, or practical by others (Chen & Trevino, 2022;Ng et al, 2022;Xu et al, 2019).…”
Section: Employee Voicementioning
confidence: 99%